Zonasi Kawasan Pesisir Makassar Berbasis Mitigasi Bencana - Christian Timang; Baharuddin Koddeng; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2013)
Currently, the coastal areas of Makassar damage caused by natural phenomena (sea level rise, erosion and sedimentation) and human activities (harvesting of mangroves and coastal development). The purpose of this study is to develop the concept of zoning in Makassar coastal area (Barombong Beach-CCC) based on disaster mitigation. Stage to achieve these objectives are: identify the characteristics associated with the level of Makassar coast disaster risk, disaster mitigation draft and provide mitigation based on the concept of zoning in the study area. This study was conducted by surveying and collecting qualitative and quantitative data using statistical data analysis techniques and analysis of disaster risks, and then discussed descriptively. The results of this study demonstrate the physical characteristics of the study area is relatively flat topography which is located at a height of 0-6 m above sea level , 0-2 % slope , landform morphology unit is an alluvial plain morphology resulting from Jeneberang River as a result of the deposition process, geological rock formed by deposition Jeneberang River sediment transport, soil type Inceptisol, bathymetric conditions to 4 nautical miles (Nautical miles) is 1.13 meters, the average tidal range between 31-0 meters below sea level, wave ranges 0.5 to 1 meter. Level disaster risk consists of two levels of risk are moderate (41%) and high risk levels (59%). The concept of disaster mitigation include Protection, Accommodation, Retreat and patterns, so that the concept of zoning-based disaster mitigation include protection zones, Zone Accommodation and Relocation zone.